Figure-of-eight brace versus sling: a retrospective cohort study of effect on shortening for displaced midshaft pediatric clavicular fractures. Issue 3 (27th May 2020) - Sugalski, Christopher; Mundy, Andrew; Buchan, Daniel; Everhart, Joshua S.; Samora, Walter P.
Abstract : Background: We sought to determine if there is a difference in clavicle shortening when utilizing figure-of-eight braces versus simple sling treatments for completely displaced midshaft fractures in the pediatric population. Methods: A pediatric level I trauma center patient database was queried for diagnosis of clavicular fracture between January 2009 and December 2014 for patients between the ages of 10 to 18 yr. Radiographs were reviewed and 100% displaced midshaft fractures identified. Initial injury and follow-up radiographs were measured for longitudinal shortening. Change in shortening was calculated as the difference in the initial injury and the follow-up measurements. Results: Records of 1153 patients with clavicular fractures were reviewed, and 126 were identified with 100% displaced midshaft fractures, adequate radiographic imaging, and nonoperative treatment. Ninety-seven patients (77%) were treated with a figure-of-eight brace. Twenty-nine patients (23%) were treated with a sling. Change in shortening was −0.4 mm and −1.9 mm for the figure-of-eight brace and sling, respectively ( P =0.14), indicating further shortening in both treatment groups. No significant differences were observed between treatment groups with respect to age, side injured, length of radiographic follow-up, initial shortening, or change in shortening. Conclusions: There is no significant difference in change in shortening for 100% displaced midshaft pediatric clavicular fractures when comparing treatment with a figure-of-eight brace versus treatment with a sling. There is a trend toward improved alignment (2.6 mm lengthening) for more significantly displaced fractures (>10 mm); however, the clinical significance of the finding is indeterminate. Level of Evidence: Level III.